Математична постановка і числовий аналіз задачі про рух повітряного потоку в циклоні - Дорундяк, Л. М.; Лютий, Є. М.; Тисовський, Л. О.; Ляшеник, А. В. (НТУ "ХПІ", 2013)
The complete set of equations for the fluid dynamics of air flow of air in the cyclone. Recorded boundary conditions on the walls of the cyclone and the exhaust pipe. Performed a numerical analysis of the problem and obtained the trajectory of the air flow.
Keywords: модель математична; гідрогазодинаміка; умови граничні; умови початкові